Constitutional amendments in India - Pylee, M. V.; India. Parliament. Lok Sabha. Secretariat (New Delhi : Universal Law Publishing Co. Pvt. Ltd., 2003)
Study; includes synopses of the Constitution Amendment Acts and full texts.
Includes bibliographical references and index.
Keywords: Constitutional amendments -- India